Determination of total phenolic and flavonoid content and evaluation of antioxidant activities of Cuscuta reflexa - Azad, Abul Kalam; Mohamed, Farahidah (Universal Journal of Pharmaceutical Research, 2024)
stems extract. Due to the reach of medicinal components, it has been using among Indian subcontinent people to treat various chronic diseases for ancient era. However, there are lacks of study on antioxidant activities of C. reflexa with its potential therapeutic compounds, therefore this study motivated to investigate more on its stems extract for further explore. Methods: Soxhlet extraction method was employed to extract phenolic compounds from C. reflexa stems. The effect of extraction time (1-4 h) and concentration of ethanol (45%, 60%, 75% and 90%) on the percentage of yield, total phenolic (TPC) and flavonoid content (TFC) was investigated. The functional groups of phenolic compounds were characterized by using Fourier Transform Infrared Spectrometry (FTIR). DPPH and ABTS•+ radical scavengers were used to evaluate antioxidant activity. Results: Data showed the highest percentage of yield (10.22±0.14% w/w), TPC (64.11±0.17%, mg GAE/g d.w.) and TFC (41.08±0.34%, mg QE/g d.w.) at 3 h with 75% ethanol. FTIR results revealed the presence of functional groups associated phenolic compounds which are the band at 1260 cm−1 illustrations the C–O groups of polyols existence and C–O–C of ester for presence of quercetin which represent the hydroxy flavonoids in the extract. DPPH and ABTS•+ radical scavengers were showed very potent antioxidant activity with IC50 295.12±1.33 and 245.43±0.78 μg/mL. Conclusion: Phenolic and flavonoids enriched C. reflexa extract may play a potential role as a natural nutritional and therapeutic source in Bangladesh.